Optimization of Co-rotating twin-screw extruders using pareto local search - Teixeira, Cristina (2010)
A Pareto Local Search (PLS) algorithm was developed and applied to the screw configuration of co-rotating twin-screw extruders. This problem can be seen as a sequencing problem where a set of different screw elements are to be sequentially positioned along the screw in order to maximize the extruder performance. The results obtained were compared with previous results obtained with a Multi-Objective Evolutionary Algorithm (MOEA), which was previously developed by the authors. These results show that the PLS algorithm, despite its conceptual simplicity, is able to generate screws with good performance.